STATE OF HAEMOMICROVASCULAR RATE OF RATS’ SUBMANDIBULAR SALIVARY GLAND AT INTRODUCTION OF CRYOPRESERVED PLACENTA AND EXPERIMENTAL SIALADENITIS - Shepitko, I.V.; Shepitko, V.I.; Yeroshenko, G.A.; Lisachenko, O.D. (World of Medicine and Biology, 2012)
On rats-males of “Vistar” line the reaction of haemomicrovascular rate was investigated at introduction of cryopreserved placenta, acute sialadenitis and it’s correction by introduction of cryopreserved placenta. Animals were destroyed from an experiment on 1, 2, 3, 5, 7, 10, 14, 21 and a 30 day.It is set that on single introduction of cryopreserved placenta a haemomicrovascular rate reacts the substantial diminishing and increase of diameters during a 2-7 days of experiment. On 14th day renewal of the studied parameters is marked to the values in control, that specifies on an insignificant immune answer and reaction within the limits of physiological. At the acute sialadenitis of change outside of haemomicrovascular rate come to light on all terms of experiment. Introduction of cryopreserved placenta on a background an experimental sialadenitis results in renewal of values of diameters of haemomicrovascular rate to the indexes in control already from a 5-7 days, that specifies on medical properties of bioactive matters of placenta.
Keywords: placenta; sialadenitis; haemomicrovascular rate